ON THE STATE OF FUNCTIONAL ACTIVITY OF THE SYMPATHETIC-ADRENAL SYSTEM AND FREE RADICAL PROCESSES IN WOMEN OF FERTILE AGE WITH METABOLIC SYNDROME - Tashtemirova Iroda Mahkambaevna; Qosimov Iqboljon Sodiqjon ogli (Scholar Express Journals, 2023)
This article shows study the relationship between disorders of the functional state of the sympathetic-adrenal system (SAS) and the processes of lipid peroxidation in women of fertile age with metabolic syndrome.
Keywords: peroxidation; sympathetic; system